Rancang Bangun Aplikasi Penentuan Rute Dan Penjadwalan Distribusi Barang Dengan Metode Clarke-Wright Saving Heuristic (Studi Kasus Ud. ABC) - Christian Chandra, Robert Elisa; Sunarto, M. J. Dewiyani; Maulana, Yoppy Mirza (Jurnal JSIKA, 2012)
“Each company that take the roles as distributor of a product certainly have a distribution plan as standard references in determining route and schedule distribution including with UD ABC Bojonegoro. The company has increased customers rapidly which affects the the increasing the mileage and transportation costs. In that case, the company need a solution that can produce route and schedule distribution capable of reducing the mileage goods distribution and transportation costs. A solution that can be used to resolve this problem is by using the Clarke-Wright Method that can produces an arrangement of routes and schedule to be passed of a vehicle in sends goods to each consumers who has committed a reservation. By using the route and schedule of the distribution of goods that are calculated from the Clarke-Wright method, it obtained result of the mileage between the calculations manually and calculation using applications decreased from 215 miles into 142 km, decreased transportation costs of Rp. 144.643,- to Rp. 91.286,- and utility vehicles increased from 87% to 98.5%.” Keywords: Distribution Route, Clarke-Wright